A Very Unlikely Finding in a Male Child: Urethral Prolapse - Çiğdem Ulukaya Durakbaşa; Gonca Gercel; Murat Huseyin Mutus; Burhan Aksu; Seyma Ozkanli (European Journal of Pediatric Surgery Reports, 2017)
Urethral prolapse is a disease of prepubertal black girls and postmenopausal women with an unknown cause. It may be congenital in origin or an acquired condition. It has never been reported in males. We report a 10-year-old Caucasian boy who presented because of recurrent right undescended testis. He had been operated on for bilateral undescended testes 7 years ago in another hospital, and circumcision was done during the same operation. The boy complained of a weak urinary stream during voiding. The physical examination was consistent with recurrent right undescended testis. Penile examination showed a circumferential urethral prolapse around the meatus. The urethral meatal appearance was apparent right after the circumcision. An orchiopexy operation as well as circumferential excision of the perimeatal urethral tissue with primary repair was done. The pathological examination of the specimen revealed keratinized stratified squamous epithelium consistent with urethral mucosa. The postoperative course was uneventful, and the patient urinates normally at the 8 postoperative month with a normal uroflowmetry study. This is the first report of urethral prolapse in a male. Because circumcision is a widely employed practice in many cultures, it is unlikely to be a predisposing factor. It is a benign condition that can be cured with simple resection and anastomosis.